Стабілізація руху візка рудно-грейферного крана - Шевченко, Іван Степанович; Морозов, Дмитро Іванович; Самчелєєв, Юрій Павлович; Дрючин, Віктор Гаврилович (НТУ "ХПІ", 2010)
In article is described system of electric drive moving the pushcart of the tap ore-grab, which provides the reduction of the slanting of the pushcart under her motion. Linearity of motion and invariance to static moment is provided by pulsed mode of the motors in the dynamic braking.
The stabilization of the moving the pushcart of the tap ore-grab
Keywords: реборд коліс; рейка; зносостійкість; експлуатація обладнання; електропривід багатодвигунний; регулятор